Sex-dependent effects of microglial reduction on impaired fear extinction induced by single prolonged stress - Torres-Rodriguez, Orlando; Ortiz-Nazario, Emily; Rivera-Escobales, Yesenia; Velazquez, Bethzaly; Colón, María; Porter, James T. (Frontiers in Behavioral Neuroscience, 2023)
Single prolonged stress (SPS) is a preclinical rodent model for studying post-traumatic stress disorder (PTSD)-like behaviors. Previously we found that increased expression of the microglial marker Iba-1 in the ventral hippocampus after SPS exposure was associated with impaired fear extinction, suggesting that microglial activity contributed to the SPS-induced behavioral changes. To test this, we examined whether reducing microglia with the colony-stimulating factor 1 receptor blocker, PLX3397, in the diet would prevent the SPS-induced extinction impairment. Male rats exposed to SPS showed enhanced fear acquisition and impaired fear extinction memory. Adding PLX3397 to the diet prevented these behavioral changes. In contrast, PLX3397 did not prevent SPS from impairing fear extinction memory in the female rats. Despite the sex-dependent behavioral effects, we found a reduced number and area fraction of Iba-1+ microglia in both male and female rats suggesting that PLX3397 had similar effects on microglia in both sexes. Altogether, these results suggest that microglia contribute to the behavioral changes induced by SPS in male but not female rats.